2023
DOI: 10.5603/fm.a2022.0007
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant completely ossified trigeminal pore and Dorello’s canal

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Folia Morphologica" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The association of ossified PSL with hypoplasia of the Dorello´s canal [3,4], has explained the mechanism of abducens nerve palsy in several pathological conditions caused by the infection and inflammation of the petrous apex [2]. Contrary to these adverse findings, studies also claimed that the ossified PSL may act as an important anatomical landmark, shielding the abducens nerve by limiting the petrous drilling in skull base surgeries [11] and may protect the structures passing through Dorello's canal as commonly seen in nonhuman primates [17,23]. A study by Ozgur and Esen [20] supported this hypothesis and revealed that the complete or partial ossification of PSL was not associated with abducens nerve palsy as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The association of ossified PSL with hypoplasia of the Dorello´s canal [3,4], has explained the mechanism of abducens nerve palsy in several pathological conditions caused by the infection and inflammation of the petrous apex [2]. Contrary to these adverse findings, studies also claimed that the ossified PSL may act as an important anatomical landmark, shielding the abducens nerve by limiting the petrous drilling in skull base surgeries [11] and may protect the structures passing through Dorello's canal as commonly seen in nonhuman primates [17,23]. A study by Ozgur and Esen [20] supported this hypothesis and revealed that the complete or partial ossification of PSL was not associated with abducens nerve palsy as in our study.…”
Section: Discussionmentioning
confidence: 99%